Self-Esteem and Self-Concept As Predictors of Adolescents' Social Media Dislike Fears - Osman SONER (Muhammed Yıldız, 2020)
This research aimed to examine adolescents' social media dislike fears in terms of various variables and to determine the relationship between self-concept and self-esteem and social media dislike fears. The study group of the research consists of 631 students, 235 (37%) boys and 396 (63%) girls studying in different high schools in Sultanbeyli district of Istanbul. Social Media Dislike Fear Scale, Rosenberg Self-esteem Scale, Self-concept Scale and a Personal Information Form were used as data collection tools. Skewness and kurtosis values were analyzed for data analysis and analyzes were performed after the extreme values of the data were cleared and normality assumption was observed. In comparisons between groups, t-test was used to compare the two groups and One-Way Analysis of Variance was used to compare more than two groups, and F statistics were used to determine the differences between groups. Standard Multiple Regression Analysis was used to determine the strength of adolescents' self-esteem and self-concepts in predicting social media dislike fear levels. According to research results; adolescents' social media dislike fears were found to differ significantly by gender, number of likes and number of friends; self-esteem does not differ according to gender, besides, self-concept differs according to gender and female students' self-concepts are higher than men’s. Female students' self-concepts are higher than men's and there is a significant relationship between the sub-dimensions of self-esteem, self-concept and social media fear of dislike scale and these two variables were found to significantly predict social media dislike fear.